Effects of Four Different Cold Storage Conditions on the Quality of Orange Juice - Lin Xian; Xu Yujuan; Wu Jijun; Chen Yulong; Wen Jing; Zhang Yan; Tang Daobang (Zhileng xuebao)
Effects of four different low storage temperatures-higher refrigeration temperature(8℃),lower refrigerated temperature(4℃), hyo-on temperature(-2℃) and freezing temperature(-20℃) on the quality of orange juice were studied. Results show that: 1)In juice stored under hyo-on storage condition, changes of soluble solid content are the smallest; total number of detected volatile flavor compounds, numbers of hydrocarbon terpenes and numbers of alcohols are the largest; relative content of alcohols and esters are the highest. 2)In juice stored under freezing storage condition, vitamin C level detected in the fifth week and relative content of aldehydes in volatile flavor compounds are the highest. 3)In juice stored under refrigeration condition, variation in content of soluble solid in the one stored under higher refrigeration temperature appears to be greater ; number of detected volatile flavor compounds is the smallest; however, relative content of hydrocarbon terpenes is the highest; relative contents of myrcene, linalool and citral are the lowest. 4)Under all storage conditions, differences in changes of total acid, pH and color of the orange juice are not significant.